2013
DOI: 10.2139/ssrn.2256511
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, Employment Growth, and Foreign Ownership of Firms - A European Perspective

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 48 publications
6
63
0
2
Order By: Relevance
“…This is quite plausible as the majority of prior studies have arrived at similar results (Dachs and Peters 2014;Harrison et al 2008;Lofsten and Lindelof 2005). It is worth noting that organizational innovation does not generally require many employees and does not aim at creating new employment.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This is quite plausible as the majority of prior studies have arrived at similar results (Dachs and Peters 2014;Harrison et al 2008;Lofsten and Lindelof 2005). It is worth noting that organizational innovation does not generally require many employees and does not aim at creating new employment.…”
Section: Discussionsupporting
confidence: 52%
“…Theoretically, classical economists emphasized that the impact of product innovation and technological innovation leads to a large, positive employment effect. Empirically, most studies have also indicated that product innovation promotes job creation (Dachs and Peters 2014;Harrison et al 2008;Lofsten and Lindelof 2005). It is worth noting that a new product developed through product innovation may completely replace an existing product, which could have a negative effect on employment generation.…”
Section: Innovation Activity and Job Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sutton 1997). In the case of foreign ownership, Dachs and Peters (2014) recently showed that employment grows slower and is also more volatile in foreign-owned firms. GDP growth is included to reflect demand conditions in a particular country.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Additionally, according to Dachs and Peters (2014) Survey, its is found that 10% of the firms innovate both in products and processes. As depicted in table 17, another important aspect related to manufacturing firms is that they tend to undertake more innovation just in processes, rather than product innovation.…”
Section: Methodsmentioning
confidence: 99%